Maxims in Karonese Song Lyrics - Rony Arahta Sembiring; Tiara K. Pasaribu; Christine O.S. Tarigan; Selfiyani Ketaren (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Maxims used as a strategy to avoid impoliteness in conversation, but highlight politeness. In this research the writer tries to obtain a clear understanding of the use of maxims that can be found in song lyric, ,in this case the writer takes songs from Karonese. The research design used quantitative descriptive approach in order to analyses 10 song lyrics written by Plato Ginting as the subject of the study. The result found all the maxims based on Leech theory, namely; Maxim of Tact, maxim of generosity, maxim of approbation, maxim of modesty, maxim of agreement and maxim of sympathy scattered throughout the song lyrics randomly. The maxims applied in relation with the meaning of every statement that had already written in the song lyrics. The writer also found 73 sentences in 10 song lyrics that had applied by maxims according to Leech theory. The use of Maxims in song lyric helps the song writer to express a politeness meaning, and shows the implementation of the title in the songs.